Polyclonal breast cancer metastases arise from collective dissemination of keratin 14-expressing tumor cell clusters - Cheung, Kevin J.; Padmanaban, Veena; Silvestri, Vanesa; Schipper, Koen; Cohen, Joshua D.; Fairchild, Amanda N.; Gorin, Michael A.; Verdone, James E.; Pienta, Kenneth J.; Bader, Joel S.; Ewald, Andrew J. (Proceedings of the National Academy of Sciences - PNAS, 2016)
Recent genomic studies challenge the conventional model that each metastasis must arise from a single tumor cell and instead reveal that metastases can be composed of multiple genetically distinct clones. These intriguing observations raise the question: How do polyclonal metastases emerge from the primary tumor? In this study, we used multicolor lineage tracing to demonstrate that polyclonal seeding by cell clusters is a frequent mechanism in a common mouse model of breast cancer, accounting for >90% of metastases. We directly observed multicolored tumor cell clusters across major stages of metastasis, including collective invasion, local dissemination, intravascular emboli, circulating tumor cell clusters, and micrometastases. Experimentally aggregating tumor cells into clusters induced a >15-fold increase in colony formation ex vivo and a >100-fold increase in metastasis formation in vivo. Intriguingly, locally disseminated clusters, circulating tumor cell clusters, and lung micrometastases frequently expressed the epithelial cytoskeletal protein, keratin 14 (K14). RNA-seq analysis revealed that K14⁺ cells were enriched for desmosome and hemidesmosome adhesion complex genes, and were depleted for MHC class II genes. Depletion of K14 expression abrogated distant metastases and disrupted expression of multiple metastasis effectors, including Tenascin C (Tnc), Jagged1 (Jag1), and Epiregulin (Ereg). Taken together, our findings reveal K14 as a key regulator of metastasis and establish the concept that K14⁺ epithelial tumor cell clusters disseminate collectively to colonize distant organs.